Factors and patterns in mobile banking and payment services use in the United States - Sinha, Gaurav R.; Mehta, Raj Chirag; Kaittila, Anniina; Viitasalo, Katri (Palgrave Macmillan Ltd., 2026)
This study seeks to identify factors and patterns affecting mobile banking and payment services use in the US. We used data from the National Financial Capacity Study, a triennial survey assessing the financial capabilities of U.S. adults. The survey was conducted between June and October 2021 using non-probability quota sampling from established online panels that recruit millions of participants for survey research, yielding a sample of over 25,000 respondents. For this study, we analyzed a subset of 20,758 respondents who provided a positive response to the main question of interest on mobile banking and payments. Using quantitative approaches, we first examined associations between financial knowledge, behaviors, and mobile banking and payment services use. Higher objective financial literacy was associated with lower mobile banking use, while subjective financial literacy and positive financial behaviors increased the likelihood of use. We then used latent class analysis to identify three distinct user groups with varying financial behaviors and mobile banking and payment services use patterns. Class 1 represents users with high financial behaviors and low MBPS users (45.4%), class 2 involves users who are low on financial behaviors and moderate MBPS users, and class 3 includes mixed financial behaviors and high MBPS users (19.7%). Our findings contribute to the literature by showing behavioral heterogeneity among mobile banking and payment services users; insights which can help policymakers, financial institutions, and service providers seeking to improve financial services access and promote financial inclusion.